Awareness, Utilization and Barriers in Accessing Assistive Technology among Patients Attending Low Vision Rehabilitation Center - Sharqa Fatima; Mehreen Tanveer; Fariha Ayub; Widat Sohail; Zahra Batool (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The UN estimates that more than one billion persons require one or more assistive devices to maintain their functioning. Aim: To determine the knowledge, adoption and utilization of assistive devices among low vision patients. methods: This cross-sectional study was conducted from September 2023 to December 2023 and consists of 130 subjects’s visits to the low vision rehabilitation centre of Al Shifa Trust Eye Hospital. The questionnaire was filled out by asking the patients enlisted questions. The frequency and percentages were generated for the qualitative variables, whereas the mean and standard deviation were generated for the quantitative variables. Results: The average age was 27.82 ± 8.65 (range 18- 50 years). By taking the mean value as a cut-off point, 58.5% of patients had poor awareness, whereas only 41.5% had good awareness of assistive technology. 75 patients Out of 130 were using some kind of assistive technology. Out of these 75, 63 patients got benefit from their prescribed devices, but 12 participants could not get any benefit. Lack of awareness and lack of training were the most frequently reported barriers in the study. Conclusion: The awareness and utilisation of assistive devices among low-vision patients is relatively low. Different strategies should be introduced to increase awareness and utilisation and to overcome the major barriers. Keywords: Low vision, Assistive technology, Artificial Intelligence